(untitled) (Indonesian Anti Corruption Studies, 2024)
State-Owned Enterprises (SOEs) in Indonesia occupy a critical space in the national economy but are often vulnerable to corruption due to weak governance and accountability mechanisms. This paper explores the corruption risks within Indonesian SOEs, analyzing regulatory frameworks, corporate governance structures, and documented corruption cases. Drawing on legal analysis, financial audits, and stakeholder interviews, the study identifies accountability gaps that facilitate corrupt practices such as embezzlement, nepotism, and procurement fraud. The research highlights the tension between political influence and commercial autonomy, which undermines effective oversight. It argues that strengthening SOE governance requires institutional reforms, enhanced transparency, and greater public scrutiny to mitigate corruption risks and align SOEs with national development goals. This study contributes to international debates on corruption in public enterprises, offering insights relevant to other emerging economies seeking to improve SOE accountability.